2022
DOI: 10.1002/admi.202201317
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependence of Interface‐Generated Spin Currents in Ferromagnet/Ti/CoFeB Trilayers

Abstract: Interface‐generated spin currents in ferromagnet (FM)/nonmagnet (NM) structures provide both in‐plane and out‐of‐plane spin–orbit torques (SOTs), enabling the field‐free switching of perpendicular magnetization of the other FM layer in magnetic trilayers. In this study, the NM thickness dependence of interface‐generated spin currents and associated SOTs in FM/Ti/CoFeB trilayers is investigated. In such magnetic trilayers, it is known that the in‐plane SOT results from the spin–orbit filtering of the interface‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Due to the spin-orbit filtering, the incoming unpolarized carriers can become spin-polarized by spindependent reflection and transmission at the interface. Moreover, it was recently reported that the sign of the spin current from the spin-orbit filtering effect is related to the magnitude of the charge current in the two materials that constitute the interface [37]. The resistivities of Ru (10 nm) and Cu (10 nm) in our study are about 9.4 and 3.8 μΩ cm, respectively.…”
Section: St-fmr Measurementsupporting
confidence: 46%
See 2 more Smart Citations
“…Due to the spin-orbit filtering, the incoming unpolarized carriers can become spin-polarized by spindependent reflection and transmission at the interface. Moreover, it was recently reported that the sign of the spin current from the spin-orbit filtering effect is related to the magnitude of the charge current in the two materials that constitute the interface [37]. The resistivities of Ru (10 nm) and Cu (10 nm) in our study are about 9.4 and 3.8 μΩ cm, respectively.…”
Section: St-fmr Measurementsupporting
confidence: 46%
“…Experimentally, Baek et al demonstrated the interface-generated spin currents in the CoFeB/Ti and NiFe/Ti bilayer structures [36]. It was also shown that the sign and magnitude of the spin currents could be modulated by adjusting the electrical conductivity of the two materials forming the interface [37]. These results suggest the great potential of well-controlled nanostructures and interfaces for improving spin-charge conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation